Given that 'y' is directly proportional to 'x',
![y\propto x](https://img.qammunity.org/2023/formulas/mathematics/high-school/l4zwk1k8ugqhz9i8ahso887j4vo9hrkqvi.png)
Let 'k' be the constant of proportionality.
Then the equation becomes,
![y=kx](https://img.qammunity.org/2023/formulas/mathematics/college/zfnjlk9kn7jg7cyy0nlnepmsiaxj3b2oge.png)
Given that 'y' is 14 when 'x' is 12,
![\begin{gathered} x=12 \\ y=14 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/78d3xxxn7p18iybndc20pxt0ug7raz4gxu.png)
Substitute the values in the equation,
![\begin{gathered} 14=k\cdot12 \\ k=(14)/(12) \\ k=(7)/(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/j806atr4haejtgl4mwufdeughh8qek4604.png)
Substitute the value of 'k' in the equation,
![y=(7)/(6)x](https://img.qammunity.org/2023/formulas/mathematics/high-school/p5rdn3w28mqr0pjvj1hvczb8d0gd8yaycb.png)
Thus, the required equation that relates 'x' and 'y' is,
![y=(7)/(6)x](https://img.qammunity.org/2023/formulas/mathematics/high-school/p5rdn3w28mqr0pjvj1hvczb8d0gd8yaycb.png)